Biological evaluation of surface-modified magnetic nanoparticles as a platform for colon cancer cell theranostics - Moskvin, Maksym; Babič, Michal; Reis, Salette; Cruz, M Margarida; Ferreira, Liliana P; Carvalho, Maria Deus; Lima, Sofia A Costa; Horák, Daniel (Colloids and surfaces. B, Biointerfaces, 2018)
Magnetic nanoparticles offer multiple possibilities for biomedical applications. Besides their physico-chemical properties, nanoparticle-cellular interactions are determinant for biological safety. In this work, magnetic nanoparticles were synthesized by one-shot precipitation or two-step reaction and coated with biocompatible polymers, such as poly(l-lysine) and poly(N,N-dimethylacrylamide-co-acrylic acid), and carbohydrates, like l-ascorbic acid, d-galactose, d-mannose, and sucrose. The resulting magnetic nanoparticles were characterized by dynamic light scattering, FT-Raman spectroscopy, transmission electron microscopy, SQUID magnetometry, and Mössbauer spectroscopy. Ability of the nanoparticles to be used in theranostic applications was also evaluated, showing that coating with biocompatible polymers increased the heating efficiency. Nanoparticles synthesized by one-shot precipitation were 50% larger (∼13nm) than those obtained by a two-step reaction (∼8nm). Magnetic nanoparticles at concentrations up to 500μgmL-1 were non-cytotoxic to L929 fibroblasts. Particles synthesized by one-shot precipitation had little effect on viability, cell cycle and apoptosis of the three human colon cancer cell lines used: Caco-2, HT-29, and SW-480. At the same concentration (500μgmL-1), magnetic particles prepared by a two-step reaction reduced colon cancer cell viability by 20%, affecting cell cycle and inducing cell apoptosis. Uptake of surface-coated magnetic nanoparticles by colon cancer cells was dependent on particle synthesis, surface coating and incubation time.
Keywords: Caco-2 Cells; magnetické nanočástice; Cell Cycle; nádorové buněčné linie; Cell cycle; apoptóza; teranostická nanomedicína; Caco-2 buňky; HT29 Cells; povrchové vlastnosti; Poly(N,N-dimethylacrylamide); Mice; Cell Line, Tumor; Magnetics; buněčný cyklus; Cellular uptake; Polymers; nádory tračníku; Surface Properties; Iron oxide nanoparticles; zvířata; Humans; Magnetite Nanoparticles; magnetismus; Colonic Neoplasms; viabilita buněk; Cell Survival; Carbohydrates; Theranostic Nanomedicine; myši; Coated Materials, Biocompatible; biokompatibilní potahované materiály; polymery; buňky HT-29; lidé; Apoptosis; Animals